Preparation of ultrafine Cu3Si in high-current pulsed arc discharge; Nanotechnologies in Russia; Vol. 11, iss. 9 - Pak A. Ya. Aleksandr Yakovlevich; Shatrova K. N. Kseniya Nikolaevna; Aktaev N. E. Nurken Erbolatovich; Ivashutenko A. S. Alexander Sergeevich (2016, 2016)
Title screen